Fabrication, characterization and drug release behaviors of chitosan microfibers loaded with herbal or non-herbal drugs. Issue 4 (3rd April 2021) - Yu, Hao-Ran; Shen, Qing
Abstract: Two chitosan, CS, microfibers loaded with the herbal persimmon leaves, PL, and the non-herbal metformin hydrochloride, MH, were wet spun, respectively. SEM images shown that these two CS microfibers have different surface morphologies at the as-spun state due to the PL-loaded fiber presented the squamae-like structure and the MH-loaded fiber presented some bright dots. This suggested that the PL and MH were loaded in the CS chains by different mechanisms and some loaded MH molecules out of the CS chains might be free and separated by spinning-induced extrusion forces. FTIR spectra analysis indicated that the PL was loaded in the CS chains mainly by the O-H groups and formed the interpenetration network and the MH was loaded in the CS chains mainly by the N-H groups and formed the sheathing structure. The loading of these herbal and non-herbal drugs in CS chains both shown good miscibility while the mechanical properties were reduced as compared with the pure CS fiber. The release of the PL and MH from CS fibers both followed the same Langmuir kinetics model, while the comparisons found that the released amount was greater for the PL and the release rate was faster for the MH.